An Integrative Model of Music Royalty Determination: Mathematical and Sharia Economic Perspectives - Agus Miftakus Surur; Hatıra Günerhan; Alwi Musa Muzaiyin; Pandi Rais; Agus Subandono; Sri Pujilestari (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
Music royalties remain a crucial yet often debated issue in Indonesia's café and restaurant sector, especially in Muslim-majority regions where legal obligations intersect with Sharia economic principles. Previous studies tend to address royalty disputes from either a legal or religious angle, leaving a gap for an integrated approach. This study seeks to fill that gap by combining a quantitative revenue estimation model with fiqh muamalah analysis to determine royalty obligations. Using Strong Coffee café as a case study, the research applies a descriptive–quantitative method. Data collection is based on operational assumptions, including average spending per customer, turnover rate, adequate seating capacity, and the applicable royalty tariff. Revenue is estimated by calculating monthly income derived from seat capacity and daily utilization, followed by a proportional royalty assessment. Findings indicate that with 69 seats, a three-time daily turnover, and an average spending of IDR 11,000, the café's monthly revenue reaches approximately IDR 31.7 million, resulting in a royalty payment of IDR 345,000. The study presents a novel perspective: royalty compliance constitutes not only a legal requirement but also a moral and religious duty under Sharia, thereby reinforcing business ethics and consumer trust. The paper concludes with recommendations for regular internal audits and Sharia-based outreach programs for policymakers. Royalti musik tetap menjadi isu penting sekaligus diperdebatkan dalam industri kafe dan restoran di Indonesia, terutama di wilayah mayoritas Muslim di mana kewajiban hukum beririsan dengan prinsip ekonomi syariah. Studi terdahulu umumnya membahas persoalan royalti dari sisi hukum atau agama secara terpisah, sehingga menyisakan celah bagi pendekatan terpadu. Penelitian ini bertujuan mengisi celah tersebut dengan mengombinasikan model estimasi pendapatan kuantitatif dan analisis fikih muamalah untuk menentukan kewajiban royalti. Studi kasus dilakukan di kafe Strong Coffee dengan menggunakan metode deskriptif–kuantitatif. Data dianalisis berdasarkan asumsi operasional meliputi rata-rata belanja per pelanggan, tingkat perputaran kursi, kapasitas efektif tempat duduk, serta tarif royalti yang berlaku. Perhitungan dimulai dari pendapatan bulanan hasil pemanfaatan kapasitas kursi, kemudian diturunkan ke jumlah kewajiban royalti. Hasil menunjukkan bahwa dengan 69 kursi, tiga kali perputaran harian, dan rata-rata belanja Rp 11.000, pendapatan bulanan mencapai sekitar Rp 31,7 juta dengan kewajiban royalti sebesar Rp 345.000. Temuan ini menegaskan kebaruan perspektif: kepatuhan royalti bukan hanya kewajiban hukum, tetapi juga tanggung jawab moral-religius dalam syariah, sehingga memperkuat etika bisnis dan kepercayaan konsumen. Penelitian menyarankan audit internal rutin bagi pelaku usaha serta sosialisasi berbasis syariah bagi pembuat kebijakan.